Soviet Tort Law: The New Principles Annotated - Gray, Whitmore (1964)
In 1961, the federal legislature, the USSR Supreme Soviet, finally adopted a skeleton code of fundamental principles of civil law.10 This recodification, which incorporates 40 years of case law and doctrinal development as well as some major innovations, will be the basis for individual civil codes to be adopted in each of the 15 union republics. While there may be some slight modifications, and certainly some variety in the degree of additional detail included in the individual codes by each republic,11 these Principles present already a fairly comprehensive picture of the shape of the future law. They are about as detailed as the tort provisions in other modem civil codes, and cover the grounds of liability, the defenses which are to be recognized, and the scope of compensable injury. In addition, they include provisions relating to workmen's compensation claims, wrongful death actions, and rules governing governmental tort liability. This article is an attempt to restate in the form of an annotation to these Principles the broad outlines of the contemporary Soviet law of tort